TRADISI JUJURAN DALAM PERNIKAHAN ADAT BANJAR PERSPEKTIF MAQASHID SYARIAH DI KECAMATAN BETARA KABUPATEN TANJUNG JABUNG BARAT - Nurhayati; Rahmi Hidayati Al Idrusiah; Hermanto Harun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to understand and analyze in depth the tradition of jujuran in Banjar traditional weddings from the perspective of maqashid sharia in Betara District. The purpose of this study is to determine whether the jujuran tradition aligns with maqashid sharia and to examine the positive and negative impacts contained within the jujuran tradition. This is a qualitative study using a field approach conducted in Betara District, West Tanjung Jabung Regency. Data collection techniques include observation, interviews, and documentation. The hypotheses in this study are: (1) the existence of a custom of carrying out the jujuran tradition in Banjar society, (2) the legal status of the jujuran tradition from the perspective of maqashid sharia, and (3) the positive and negative impacts of the jujuran tradition. Hypotheses were tested using descriptive analysis by grouping and interpreting data. This research yields three results, namely: (1) the occurrence of the practice of jujuran in Betara District, which can be categorized as urf sahih as long as it does not cause a burden (musyaqqah) for the groom, (2) maqashid sharia with the practice of jujuran has an important functional relationship to the protection of the five main elements of sharia (al- daruriyyat al-khamsah), as long as it does not cause a burden for the groom, (3) there are positive impacts that bring benefits to both families, however, negative impacts on the practice of jujuran will occur when it is not implemented proportionally. The conclusion of this research is that the practice of the jujuran tradition can still be carried out, because it has an important functional relationship to the protection of the five main elements of sharia (al- daruriyyat al-khamsah) by placing custom as a means of realizing the sacred purpose of marriage. However, it is necessary to continue to internalize the values of deliberation in the jujuran tradition to ensure that the practice remains within the corridor of benefits that are in line with the spirit of Islamic law. Furthermore, moderation is necessary so that traditions continue to function as instruments of glorification without neglecting the principle of convenience (taysir)